2015
DOI: 10.3168/jds.2014-9075
|View full text |Cite
|
Sign up to set email alerts
|

Cow-to-cow variation in fibroblast response to a toll-like receptor 2/6 agonist and its relation to mastitis caused by intramammary challenge with Staphylococcus aureus

Abstract: Staphylococcus aureus is a common cause of chronic mammary gland infections in dairy cattle. However, the inflammatory response and duration of infection following pathogen exposure is variable between individual animals. To investigate interanimal differences in immune response, dermal fibroblast cultures were established from skin biopsies collected from 50 early lactation Holstein cows. The fibroblasts ability to produce IL-8 in response to a 24-h treatment with a synthetic toll-like receptor 2/6 agonist (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 73 publications
(73 reference statements)
3
20
0
1
Order By: Relevance
“…Finally, no difference was measured between HR and LR animals in their E. coli-specific circulating IgG response and, importantly, antibody response did not correlate with ability to clear infection. This result agrees with previous literature stating that antibody response is not a major contributor to E. coli or S. aureus clearance within the mammary gland (Benjamin et al, 2015;Herry et al, 2017). The role of the adaptive response in determining between-cow differences in mastitis severity and duration should be the subject of future research, specifically the role of Th-17 cells, which have been shown to be the predominant T-cell responder in E. coli mastitis (Porcherie et al, 2016) and are associated with a primarily neutrophilic response.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Finally, no difference was measured between HR and LR animals in their E. coli-specific circulating IgG response and, importantly, antibody response did not correlate with ability to clear infection. This result agrees with previous literature stating that antibody response is not a major contributor to E. coli or S. aureus clearance within the mammary gland (Benjamin et al, 2015;Herry et al, 2017). The role of the adaptive response in determining between-cow differences in mastitis severity and duration should be the subject of future research, specifically the role of Th-17 cells, which have been shown to be the predominant T-cell responder in E. coli mastitis (Porcherie et al, 2016) and are associated with a primarily neutrophilic response.…”
Section: Discussionsupporting
confidence: 91%
“…Adjusted rank, ranging from −1.50 to 2.33 for IL-8 ( Figure 1A) and from −1.65 to 2.54 for IL-6 ( Figure 1B), was used as response variable. As with previous experiments (Kandasamy et al, 2011;Benjamin et al, 2015), a large range in response to LPS was measured in conditioned medium, with a significant correlation between LPS-induced IL-6 and IL-8 production (data not shown; R 2 = 0.28, P < 0.0001).…”
Section: Dermal Fibroblast Response To Lpssupporting
confidence: 78%
See 2 more Smart Citations
“…Previous work from our laboratory and others has shown that dairy cattle manifest a wide range of immune responses following experimentally induced E. coli (Kornalijnslijper et al, 2003;Bannerman et al, 2004;Kandasamy et al, 2011) or Staphylococcus aureus (Schukken et al, 1999;Bannerman et al, 2004;Benjamin et al, 2015) mastitis. Some animals exhibit a much more robust inflammatory response during mastitis, characterized by high levels of IL-8, IL-6, and TNF-α, which can lead to severe clinical symptoms and damage to the mammary tissue.…”
Section: Discussionmentioning
confidence: 93%